Estabishment of Agrobacterium-mediated transient expression system in Betula platyphylla - Wang Lina (IJRDO-Journal of Applied Science, 2018)
Transient transformation systems have been developed as quick and convenient method and the Agrobacterium-mediated transient expression is a powerful tool for the characterization of gene function in plants. Here, we have established in vivo transient transformation system with GFP as a reporter gene by Agrobacterium-mediated of roots of Betula platyphylla. The results exhibited that the effect of infection on Betula platyphylla roots was the same as that of the whole plant and the expression level of GFP increased obviously. So,we have developed a simple and highly efficient transient transformation system that can quickly analyze the gene function in Betula platyphylla.